2015
DOI: 10.1103/physrevb.91.134425
|View full text |Cite
|
Sign up to set email alerts
|

Muon spin rotation and neutron scattering study of the noncentrosymmetric tetragonal compoundCeAuAl3

Abstract: We have investigated the noncentrosymmetric tetragonal heavy fermion compound CeAuAl 3 using muon spin rotation (μSR), neutron diffraction (ND), and inelastic neutron scattering (INS) measurements. We have also revisited the magnetic, transport, and thermal properties. The magnetic susceptibility reveals an antiferromagnetic transition at 1.1 K with, possibly, another magnetic transition near 0.18 K. The heat capacity shows a sharp λ-type anomaly at 1.1 K in zero field, which broadens and moves to a higher tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 48 publications
6
29
3
Order By: Relevance
“…2 B ). The energy of this transition is in excellent agreement with previous time-of-flight neutron spectroscopy and bulk data in a polycrystalline sample, which, however, did not allow a search for a momentum dependence (50, 54). The weak nondispersive excitation at EnormalVnormalBnormalS=7.9 normalmnormalenormalV (Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…2 B ). The energy of this transition is in excellent agreement with previous time-of-flight neutron spectroscopy and bulk data in a polycrystalline sample, which, however, did not allow a search for a momentum dependence (50, 54). The weak nondispersive excitation at EnormalVnormalBnormalS=7.9 normalmnormalenormalV (Fig.…”
Section: Resultssupporting
confidence: 87%
“…1 A ), a member of the normalCnormalenormalTnormalAnormall3 series (T = Ce, Au, Pd, Pt) and thus the wider family of normalBnormalanormalAnormall4-type materials (52). Early measurements of the bulk and transport properties of polycrystalline samples established normalCnormalenormalAnormalunormalAnormall3 as a Kondo lattice compound stabilizing incommensurate antiferromagnetic order below TnormalN=1.32 K (50, 54). The enhancement of the linear temperature dependence of the specific heat and quadratic temperature dependence of the resistivity (γ=227 mJmol1normalK2 and A=5 normalμnormalΩnormalcnormalmnormalK2, respectively) are characteristic of a heavy Fermi liquid state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In CeCuAl 3 it has been reported that they are low lying with ∆ 1 =15 K and ∆ 2 = 238 K [8,25]. Further for CeAuAl 3 excited levels of ∆ 1 =57 K and ∆ 2 = 265 K [32] Magnetic ground states in CeTX 3 compounds are usually antiferromagnetic, as in CeCuAl 3 with T N = 2.1 K and CeAuAl 3 with T N = 1.32 K. However, the exact magnetic ground states are more complicated, with a propagation vector k = (0.4, 0.6, 0) in the case of CeCuAl 3 [20] and k = (0, 0, 0.52) for CeAuAl 3 [1]. CeAgAl 3 is a rare example of ferromagnetic Ce-compound below the ordering temperature of T = 3.2 K. CePdAl 3 is reported to order antiferromagnetically below 6 K, CePtAl 3 exhibits spin-glass behaviour below 0.8 K.…”
Section: Introductionmentioning
confidence: 99%
“…Under pressure, T N rises up to 60 kbar in CeCuAl 3 and suddenly vanishes at 80 kbar [18,30], pointing towards the existence of a quantum critical point (QCP). Recently, a phonon -crystal field quasibound state has been found in CeCuAl 3 [2], which is not present in CeAuAl 3 [1]. Furthermore, a low energy anomalous excitation [4] and phonon scattering by Ce magnetic moment fluctuations are reported in CeAuAl 3 [5], as well as a possible second phase transition at 0.18 K [1].…”
Section: Introductionmentioning
confidence: 99%